2013
DOI: 10.1073/pnas.1300390110
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease activity of Saccharomyces cerevisiae Dna2 inhibits its potent DNA helicase activity

Abstract: Dna2 is a nuclease-helicase involved in several key pathways of eukaryotic DNA metabolism. The potent nuclease activity of Saccharomyces cerevisiae Dna2 was reported to be required for all its in vivo functions tested to date. In contrast, its helicase activity was shown to be weak, and its inactivation affected only a subset of Dna2 functions. We describe here a complex interplay of the two enzymatic activities. We show that the nuclease of Dna2 inhibits its helicase by cleaving 5′ flaps that are required by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(128 citation statements)
references
References 53 publications
14
114
0
Order By: Relevance
“…The physiological role of the Dna2 helicase is not yet clear. The DNA unwinding activity of Dna2 is vigorous, comparable with the helicase capacity of Sgs1, yet it is cryptic and only becomes apparent upon inactivation of the Dna2 nuclease (79). It is tempting to think that the helicase of Dna2 functions in concert with that of Sgs1 (28).…”
Section: Sgs1-dna2 Resection Pathwaymentioning
confidence: 99%
“…The physiological role of the Dna2 helicase is not yet clear. The DNA unwinding activity of Dna2 is vigorous, comparable with the helicase capacity of Sgs1, yet it is cryptic and only becomes apparent upon inactivation of the Dna2 nuclease (79). It is tempting to think that the helicase of Dna2 functions in concert with that of Sgs1 (28).…”
Section: Sgs1-dna2 Resection Pathwaymentioning
confidence: 99%
“…The Dna2 helicase exhibits only a weak 5 0 -3 0 unwinding activity on dsDNA and depends on the binding to free DNA ends before acting as a helicase (Bae et al 2002). However, recently, it was shown that Dna2 is a vigorous 5 0 -3 0 helicase in an S. cerevisiae nuclease dead mutant (Levikova et al 2013). Apparently, Dna2 depends on the binding to 5 0 -ssDNA flaps for processive helicase activity, and these flaps are degraded by the Dna2 nuclease domain of the wild-type protein (Levikova et al 2013).…”
Section: Structural Mechanisms Of Recombinationmentioning
confidence: 99%
“…However, recently, it was shown that Dna2 is a vigorous 5 0 -3 0 helicase in an S. cerevisiae nuclease dead mutant (Levikova et al 2013). Apparently, Dna2 depends on the binding to 5 0 -ssDNA flaps for processive helicase activity, and these flaps are degraded by the Dna2 nuclease domain of the wild-type protein (Levikova et al 2013). There may be a structural switch in Dna2 that regulates the balance between its nuclease and helicase activities.…”
Section: Structural Mechanisms Of Recombinationmentioning
confidence: 99%
“…Studies in Xenopus egg extracts as well as human cells show that another RecQ family of helicase Werner syndrome RecQ-like helicase (WRN) also promotes resection by unwinding the DNA ends and making it accessible for Dna2 [115][116][117][118][119]. Although Dna2 functions as both a helicase and a nuclease, only the nuclease activity is essential for the extension of DNA end resection [87,120,121]. The long stretch of ssDNA generated by Exo1 and Dna2 serves as the substrate for HR, and in the meantime prevents repair by NHEJ or MMEJ [9,92].…”
Section: Extension Of Resection By Exo1 and Dna2mentioning
confidence: 99%